Economic and Environmental Sustainability of Various Solar Thermal Devices: ECONOMIC AND ENVIRONMENTAL SUSTAINABILITY OF SOLAR DEVICES - Poonia, Surendra; A K Singh (Annals of Arid Zone, 2024)
The development of a region depends on energy utilization. The use of traditional energy sources, such as coal, oil, and natural gas cause pollution by releasing greenhouse gases into the atmosphere. To solve these environmental problems, it is important to switch to cleaner, more energy-efficient sources such as renewable energy (solar, wind, hydro, geothermal) and reduce electricity use. ICAR-CAZRI, Jodhpur has designed and constructed many new solar thermal and photovoltaic systems to provide green solutions to energy problems in arid regions. PVT (Photovoltaic-Thermal) with great potential to add energy includes hybrid and tilt-type solar dryers, trackless solar cookers, animal feed solar cookers and solar desalination units. To start a new business, the profitability of the business should be evaluated separately based on economic analysis. Banks provide loans according to the economic characteristics of the project. For this reason, the economic evaluation of solar thermal devices were carried out to evaluate the feasibility of solar technology investment in order to guide new entrepreneurs. Therefore, the cost-economics of these devices have been carried out. The high cost of business characteristics such as benefit-cost ratio (BCR), net present value (NPV), annual income, rate of return (IRR) and low cost of payback period indicate that the use of solar energy is profitable. . It also keeps the environment clean by eliminating carbon dioxide emissions.